ENGLISH TEACHERS’ PROBLEMS IN IMPLEMENTING CONEXTUAL TEACHING AND LEARNING IN JUNIOR HIGH SCHOOL - Vani Luciana Br. Sinaga; Fahri Haswani (Universitas Negeri Medan, 2022)
This research has two aims: (1) To investigate teacher’s problems in implementing CTL in teaching (2) To describe the strategies used by teachers to solve the problems. The research was conducted by using descriptive qualitative analysis. It was completed at SMP NEGERI 37 Medan. The data were gathered by interviews and classroom observation. From the result of the research, It was found that the first teacher has some problems in implementing CTL. The problems are students were shy to speak up in the class because they had lack of vocabulary. Students think that their pronunciation is bad so that it makes them afraid of being wrong and make them are not active in the class, and the problems in implementing CTL for the second teachers are lack of students interest in learning English so it makes students do not focus in learning. The students also do not have confident to present in front of the class, so that the strategy of CTL does not work well. As a result of the research, the problems of teachers in implementing CTL is students don’t have confident to speak up in the classroom and the students are also lack of interest in learning so they less practice their English. Every English teacher uses different strategies in implementing CTL to make students interest and not get bored in learning process. Keywords: Teachers,CTL,and Strategies